Addressing challenges for youths with mobility devices in winter conditions. Issue 1 (2nd January 2018) - Morales, Ernesto; Lindsay, Sally; Edwards, Geoffrey; Howell, Lori; Vincent, Claude; Yantzi, Nicole; Gauthier, Véronique
Abstract: Purpose: Winter-related research about the experience of navigating in the urban context has mostly focused on the elderly population with physical disabilities. The aim of this project was to explore potential design solutions to enhance young people's mobility devices and the built environment to improve accessibility and participation in winter. Methods: A multi-method qualitative design process included the following steps: (1) in-depth interviews; (2) photo elicitation; (3) individual co-design sessions; and (4) group co-design sessions (i.e., focus group). The participants were 13 youths (nine males and four females), aged 12–21, who used a wheelchair (12 power chair users and one manual wheelchair), for some with their parents, others without their parents, according to the parents' willingness to participate or not in the study ( n = 13). The first two authors conducted group co-design sessions with mechanical engineers and therapists/clinicians in two Canadian cities to discuss the feasibility of the designs. Results (findings): The youths and their parents reported different winter-related challenges and proposed specific design solutions to enhance their participation and inclusion in winter activities. Seven of these designs were presented at two group co-design sessions of therapists/clinicians and engineers. Two designs were found to be feasible: (1) a traction device for wheelchairs in snow and (2) a mat made of rollers to clean snow and dirt from tires. The results of this research highlight the frustrations and challenges youths who use wheelchairs encounter in winter and a need for new solutions to ensure greater accessibility in winter. Conclusions: Therapists/clinicians and designers should address winter-related accessibility problems in areas with abundant snow. Implications for Rehabilitation: Several studies show that current urban contexts do not necessarily respond accurately to the needs of individuals with limited mobility. Winter-related research about the experience of navigating in the urban context is limited and has mostly focused on the elderly population with physical disabilities. Our results clearly show that youth who use mobility devices want to be able to get around in the snow, wander outdoors, play and enjoy social participation in activities with their peers and friends. Our findings provide a starting point for the development of additional studies to seek a better understanding of the person–environment interaction in winter conditions, with tangible results in the form of better design solutions. Clinicians and designers must address such issues in northern countries and areas where snow is abundant.